2017
DOI: 10.2139/ssrn.3079833
|View full text |Cite
|
Sign up to set email alerts
|

Retirement Prospects for the Millennials: What Is the Early Prognosis?

Abstract: is to produce first-class research and forge a strong link between the academic community and decision-makers in the public and private sectors around an issue of critical importance to the nation's future. To achieve this mission, the Center sponsors a wide variety of research projects, transmits new findings to a broad audience, trains new scholars, and broadens access to valuable data sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Johnson et al (2017) projects future retirement income for older Millennials and Generation Xers and finds that median income at age 70 for members of these groups will be higher than that of prior generations, though a smaller share of individuals will have enough to maintain their preretirement standard of living. These results, as the authors describe, are uncertain, given that today's young adults still have decades of work until their retirement.…”
mentioning
confidence: 99%
“…Johnson et al (2017) projects future retirement income for older Millennials and Generation Xers and finds that median income at age 70 for members of these groups will be higher than that of prior generations, though a smaller share of individuals will have enough to maintain their preretirement standard of living. These results, as the authors describe, are uncertain, given that today's young adults still have decades of work until their retirement.…”
mentioning
confidence: 99%
“…Putting together all of these factors is beyond the scope of this paper. However, Johnson et al (2017) projects future retirement income for older Millennials and Generation Xers and finds that median income at age 70 for members of these groups will be higher than that of prior generations, though a smaller share of individuals will have enough to maintain their pre-retirement standard of living. These results, as the authors describe, are uncertain, given that today's young adults still have decades of work until their retirement.…”
Section: Discussionmentioning
confidence: 99%
“…Baby -boom 1946-1964Gen X 1965-1980Millennial 1981-1996 Number While some research has found that pay and extrinsic rewards are important to Millennials in the labor market (e.g., Leveson & Joiner, 2014), Johnson et al (2018) find that pay is less important than other factors for Millennials in switching out of jobs in the non-profit sector; Smith (2010) reports that Millennials have said they are willing to give up higher pay for more vacation and/or more flexible work arrangements; and Calk and Patrick (2017) find that the most important characteristics of a job for Millennials are recognition, rewards for performance, and feeling part of the team. The sources of Millennials' job satisfaction are consistent with having been conditioned (by us, their parents) to focus on effort over achievement and being rewarded for participation over performance (see Ng & Johnson, 2015).…”
Section: Variablementioning
confidence: 99%